Pengelompokkan Zona Belajar Anak Melalui Perencanaan Diskusi Kelas Berbasis Digital di MAN 1 Langsa - Cahya, Uci Dwi; Yusra, Syarifah (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
ABSTRAK This community service activity in the form of assistance in developing learning media aims to provide knowledge about learning methods by grouping digital based learning zones. The ability to develop learning media is expected to accelerate and facilitate teachers in carrying out the learning process. The targets in this service activity are all 26 teachers of MAN 1 Langsa. Assistance in the development of learning media is carried out by means of lectures, demonstrations and exercises accompanied by questions and answers. The lecture method is used to explain the introductory concept of professional teachers and the theory of learning media. The demonstration method is used to show a work process, namely the stages of developing digital-based learning media, while the training method is to practice learning methods. While the question and answer method is to give participants the opportunity to consult in overcoming obstacles in the development of learning media. The availability of adequate experts in the development of learning media, the enthusiasm of the participants, the support of the school principal for the implementation of activities and supporting funds from the faculty are the supporters of the implementation of this PKM activity. The obstacles faced were that teachers did not have initial knowledge about utilizing digital in the learning process and limited time for training. The benefits that participants can get from this service activity include being able to compile and develop digital-based learning media according to the courses being taught.